2017
DOI: 10.1098/rsfs.2016.0035
|View full text |Cite
|
Sign up to set email alerts
|

Representation of different exact numbers of prey by a spider-eating predator

Abstract: Our objective was to use expectancy-violation methods for determining whether Portia africana , a salticid spider that specializes in eating other spiders, is proficient at representing exact numbers of prey. In our experiments, we relied on this predator's known capacity to gain access to prey by following pre-planned detours. After Portia first viewed a scene consisting of a particular number of prey items, it could then take a detour during which the scene wen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 76 publications
2
32
0
Order By: Relevance
“…However, control experiments suggested that this ant species discriminate among nest sites by relying on the summation of light levels within nesting entrances rather than counting the exact number of available cavity entrances. Thus, the results found by Franks et al () and other studies (Cross & Jackson, ; Nelson & Jackson, ) have highlighted the need for carefully considering alternative explanations before concluding that animals attend to strictly numerical information.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, control experiments suggested that this ant species discriminate among nest sites by relying on the summation of light levels within nesting entrances rather than counting the exact number of available cavity entrances. Thus, the results found by Franks et al () and other studies (Cross & Jackson, ; Nelson & Jackson, ) have highlighted the need for carefully considering alternative explanations before concluding that animals attend to strictly numerical information.…”
Section: Introductionmentioning
confidence: 86%
“…Ladybirds, ants, beetles, and spiders assess the number of potential competitors when searching for food sources or selecting potential mates to avoid conflicts (Carazo, Fernández‐Perea, & Font, ; Hemptinne, Dixon, & Coffin, ; Nelson & Jackson, ; Tanner, ). However, studies on invertebrates have not gone especially far toward disentangling which attributes are exploited in quantity discrimination (but see Cross & Jackson, ; Nelson & Jackson, ; Yang & Chiao, ). The core distinction is between analogue variables (e.g., continuous features of stimuli as the overall surface encompassed by stimuli) and discrete variables (e.g., individuated single items within groups corresponding to exact, discrete numbers).…”
Section: Introductionmentioning
confidence: 99%
“…Arthropods appear able to perform a variety of complex tasks, ranging from spatial navigation (Menzel et al, 2005;Wehner, 2003) to object perception (van Hateren, Srinivasan, & Wait, 1990), learning (Hammer & Menzel, 1995), numerical competences (Cross & Jackson, 2017;Dacke & Srinivasan, 2008;Nelson & Jackson, 2012) and even more complex skills, such as self-recognition (Cammaerts & Cammaerts, 2015) and the cultural spreading of learned abilities (Alem et al, 2016). Among arthropods, a family of spiders has caught the interest of scientists: Salticidae.…”
mentioning
confidence: 99%
“…Cross & Jackson [34] detail an experimental test for numerical cognition in the Portia jumping spider, from which they conclude that these arachnids appear to represent the quantities '1' and '2' as discrete numerical categories; moreover, they likely discriminate among these through a method other than, for example, relying on discriminating between the timing of different sets of events. Their experimental set-up relies on the spiders' well known ability to select the most effective path (which is not necessarily the most direct one) in pursuit of prey, which is itself suggestive of the possession of a cognitive map, or an internal representation of the relationship among objects in an environment.…”
Section: Rsfsroyalsocietypublishingorg Interface Focus 7: 20170029mentioning
confidence: 99%